2019
DOI: 10.1001/jamanetworkopen.2019.9557
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Differences in End-of-Life Burdensome Interventions and Antibiotic Therapy in Nursing Home Residents With Advanced Dementia

Abstract: Key Points Question What are the population-based frequency, factors, and sex-specific differences in burdensome interventions and antibiotic therapy at the very end of life among nursing home residents with advanced dementia? Findings In this population-based cohort study of 27 243 decedent nursing home residents with advanced dementia, men were statistically significantly more likely than women to experience burdensome interventions (ie, transitions of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 67 publications
1
30
0
Order By: Relevance
“…Alternatively, a palliative care physician might have been involved in situations involving complicated goals of care discussions if discordance in care plans existed between patients with dementia or their caregivers and their treating physicians. Previous work has shown a concerning rate of potentially burdensome interventions delivered in acute care settings near the end of life in this vulnerable population, especially for those who live in nursing homes 35859. In our study, 72% of patients who died from dementia lived in a nursing home.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Alternatively, a palliative care physician might have been involved in situations involving complicated goals of care discussions if discordance in care plans existed between patients with dementia or their caregivers and their treating physicians. Previous work has shown a concerning rate of potentially burdensome interventions delivered in acute care settings near the end of life in this vulnerable population, especially for those who live in nursing homes 35859. In our study, 72% of patients who died from dementia lived in a nursing home.…”
Section: Discussionmentioning
confidence: 65%
“…Patients nearing the end of life often have high rates of costly healthcare, including emergency department visits and admissions to hospital, which could be avoidable 1. These potentially burdensome interventions are associated with poor quality of life 12345678. Consequently, the demand for palliative care is rapidly growing.…”
Section: Introductionmentioning
confidence: 99%
“…Sex affects the etiology, pathological symptoms, and therapeutic outcomes of several neurologic diseases. Initial studies suggested that AD prevalence is higher in women than in men, and the median age of death among women with advanced dementia is higher than that among men, but females live longer than males because of fewer comorbidities [9][10][11]. Sex also influences the effect of AD risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…In residents both with and without dementia, men were more likely to receive new medications of questionable benefit prior to death. A previous study has pointed toward sexspecific differences in dementia care, with men more commonly receiving burdensome interventions at the end of life [53]. The differences between men and women may be more related to social contexts than biological phenomena, i.e., gender-based differences in the provision of care or different attitudes toward death [53][54][55].…”
Section: Comparison With Other Studiesmentioning
confidence: 98%